2004
DOI: 10.1177/0731684404033961
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Absorption Behavior of Carbon Fiber-Reinforced Monomer Casting Nylon Composites

Abstract: A series of tests were conducted to study the moisture absorption behaviors of carbon fiber-reinforced monomer casting nylon (CF/MC) composites with fiber contents of 10 and 15 vol.%, and their effects on mechanical properties. The results show that the moisture absorption behavior of the CF/MC composites obeys a Fickian relationship. The maximum moisture uptake has been found to decrease with the increase of carbon fiber volume fraction. The moisture absorption rate and the time to reach the saturation fall a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Wan et al observed the decrement in time taken to reach saturation level and the rate of absorption when the temperature of medium increased [ 92 ]. This may be caused by the severe extensive corrosion of the fibre composite surface and its interior caused by temperature, thus loosening the interface of the carbon fibre matrix [ 93 ].…”
Section: Degradation Of Recycled Carbon Fibre Compositesmentioning
confidence: 99%
“…Wan et al observed the decrement in time taken to reach saturation level and the rate of absorption when the temperature of medium increased [ 92 ]. This may be caused by the severe extensive corrosion of the fibre composite surface and its interior caused by temperature, thus loosening the interface of the carbon fibre matrix [ 93 ].…”
Section: Degradation Of Recycled Carbon Fibre Compositesmentioning
confidence: 99%
“…18,19 It has also been reported that long interaction of FRC's into these trapped fluid droplets may cause swelling of matrix that leads to residual stresses and degradation of fatigue, shear and impact characteristics. 20,21 Aforementioned apprehensions inspired researchers to investigate controlled use of cutting fluids as well as alternative methods for handling grinding temperature. As an example, Cong et al 22 used cold air as a cooling medium for carbon fibre reinforced polymer (CFRP) composite machining.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of natural fibres, the moisture can also influence its hydrophilic groups and promote the formation of intermolecular bonding of hydrogen with fibres that may weaken the fibre-matrix interface and may result in diminution of mechanical properties (shear strength, impact resistance, flexural strength, fatigue strength, etc. ), 30,31 shown in Figure 2. Hence, it can be determined that application of cutting fluids is highly sensitive to the defects that may be induced during machining of FRP composites.…”
Section: Introductionmentioning
confidence: 99%